(14x2+6x)=(55+13x2)

Simple and best practice solution for (14x2+6x)=(55+13x2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (14x2+6x)=(55+13x2) equation:



(14x^2+6x)=(55+13x^2)
We move all terms to the left:
(14x^2+6x)-((55+13x^2))=0
We get rid of parentheses
-((55+13x^2))+14x^2+6x=0
We calculate terms in parentheses: -((55+13x^2)), so:
(55+13x^2)
We get rid of parentheses
13x^2+55
Back to the equation:
-(13x^2+55)
We add all the numbers together, and all the variables
14x^2+6x-(13x^2+55)=0
We get rid of parentheses
14x^2-13x^2+6x-55=0
We add all the numbers together, and all the variables
x^2+6x-55=0
a = 1; b = 6; c = -55;
Δ = b2-4ac
Δ = 62-4·1·(-55)
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{256}=16$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-16}{2*1}=\frac{-22}{2} =-11 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+16}{2*1}=\frac{10}{2} =5 $

See similar equations:

| (2x^2+7x-12)-(x^2-16)=0 | | 18+x=-4x-42 | | (9x)(9x)(9x)-9x=0 | | C=12+-1b | | 5^2+6^2=x^2 | | 4x^2-200x+625=0 | | 5^2+62^2=x^ | | 150000000=300000t | | (x-9)^=36 | | (2x^2+7-12)-(x^2-16)=0 | | (14x+6x)=(55+13x) | | 2x+1/3+3x+7/5=x+14/5 | | 18y^=2-9y | | (2x+1)/3+(3x+7)/5=(x+14)/5 | | 2/3(x-9)=-5 | | x^=9 | | -3x+47=-43+2x | | 2x^=3x | | x^-6x-2=0 | | -5(x+1)=3x=6-(4x-3) | | 3x=4x-x+5 | | (x+2)^2-x^2=0 | | 12x+18=12-7 | | 3^2x+5=13 | | (x)(x)-6x-2=0 | | (x-4^2)=100 | | Y=18000-1500x | | (z+3)(z+3)=-9 | | 3x/5=6/2 | | (z+3)2=-9 | | 22.5+6x=303 | | 4a2-4=0 |

Equations solver categories